Lived Experiences of Asian and Latinx Online Doctoral Students. Issue 2 (3rd April 2021) - Natal, Maria; Jimenez, Richard; Htway, Zin
ABSTRACT: Over the past two decades, Asian and Hispanic immigrants who have been living in the United States for ≥ 10 years has increased substantially. Yet, Asian and Latinx students are behind Caucasians in doctoral degree completion rates. Enhancing enrollment, time-to-completion rates, and decreasing attrition, are of national concern among promoters of higher educational for these groups. We conducted a phenomenological study to explore the lived experiences of seven Asian and 10 Latinx online doctoral students (N = 17). Participants were recruited using nonrandom purposive convenience sampling and snowball techniques. Data were collected by one of three members of the research team. The other two research team members independently coded and conducted the thematic analysis of the de-identified transcribed interviews and reached consensus for inter-rater reliability. The major findings were that both Asian and Latinx students experienced a sense of duty and rely on family to earn a doctoral degree. Asian students were typically not the first in their families to pursue a doctorate whereas Latinx students usually were. Asian students feel pressure to succeed in the "respectable professions" by their families. Latinx students rely on "cultural capital" to succeed. Language barriers were more of a challenge for Latinx students than for Asian students. Asian and Latinx students desire shorter timeframes for feedback. The research implications include that integrating a limited amount of synchronous teaching could improve their feeling of cohesiveness which coincides with collectivism. Also, shortening timeframes for feedback during the dissertation phase could impact time to completion and decrease attrition rates.